Reflected solutions of BSDEs driven by G-Brownian motion - Hanwu Li; Shige Peng; Abdoulaye Soumana Hima (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
In this paper, we study the reflected solutions of one-dimensional backward stochastic differential equations driven by G-Brownian motion (RGBSDE for short). The reflection keeps the solution above a given stochastic process. In order to derive the uniqueness of reflected G-BSDEs, we apply a "martingale condition" instead of the Skorohod condition. Similar to the classical case, we prove the existence by approximation via penalization.
urn:nbn:de:0070-pub-29304283
Keywords: 330; G-expectation; G-BSDEs; reflected G-BSDEs